Development of STEM-Based Learning “Car Balloons” to Support Pancasila Students Profiles - Andi Eka Wulandari; Dea Puspita Sari; Enditiyas Pratiwi; Irianto Aras (STAI Hubbulwathan Duri, 2023)
The concept of an independent learning curriculum issued by the government has the aim of liberating education so that students can think and innovate freely. One way to support the independence of student education is to make adjustments in the learning process, especially in elementary schools. Therefore, this study develops learning on a STEM basis to support the profile of Pancasila students. This study uses the ADDIE method, which has five stages: analyze, design, develop, implement, and evaluate. The results showed that STEM-based learning could support the profile of Pancasila students. The teaching modules developed are on valid criteria, with a score range of 4≤ V 5. Likewise, the practicality of the module is a very practical criterion, with a score of 5. Student responses to STEM-based learning indicate that it can help support the achievement of the Pancasila student profile, namely critical reasoning, cooperation, and independence. In addition, the developed teaching modules can also help the learning process that is meaningful, fun, and interesting so that it can improve students' understanding as evidenced by the percentage of students' completeness that reaches 100% and is in very good criteria. Based on the study results, it can be concluded that the STEM-based learning module has met the valid, practical, and effective criteria for use in student learning in elementary schools.